The effects of network structure on research innovation: an analysis from a content perspective using the data of R&D funding. Issue 12 (2nd December 2019) - Pan, Wenhui; Zhao, Pengwei; Ding, Xianfeng
ABSTRACT: Technological investment aims to improve research innovation with involving many aspects, resulting in various networks. Previous studies mainly focused on collaboration relationships. In fact, research innovation can also be affected by research content. In this paper, a content perspective is proposed to construct network and analyse network structure's effect on research innovation. Furthermore, networks are divided into high and low groups to test whether network structure's effects are consistent in networks with different research innovation. Using R&D funding, the results indicate that in networks constructed from a content perspective, centralisation and density negatively affect research innovation. Average distance has a significantly positive effect on research innovation, while structural holes have a U-shaped effect on research innovation. Furthermore, it shows that in networks constructed from a content perspective, network structure's effect on research innovation in high innovation networks is larger than that in low innovation networks. We offer recommendations for government agencies regarding the design of investment schemes and for scholars regarding how to select appropriate content.